Kawasaki disease refractory to standard treatments that responds to a combination of pulsed methylprednisolone and plasma exchange: Cytokine profiling and literature review. Issue 2 (August 2015) - Matsui, Motohiro; Okuma, Yoshiaki; Yamanaka, Junko; Uryu, Hideko; Sato, Noriko; Shichino, Hiroyuki; Matsushita, Takeji
Highlights A combination of IVMP and PE was effective for a severe KD case. Our literature review revealed PE treatment was effective 93.5% of cases. Cytokine profiling showed PE decreased IL6, while sTNF-αR remained at high levels. Cytokine profiling showed PE and IVMP decreased both of IL-6 and sTNFα-R.